Exploring the lived experiences of rural school counselors who also hold teaching duties - Wright, Kristin Simoneau (My University, 2026)
Rural school districts face unique challenges, including geographic isolation, limited access to mental health services, and persistent staffing and budget constraints. In response to these pressures, some rural districts have assigned school counselors additional teaching responsibilities in addition to their counseling roles. While prior research has examined the challenges faced by rural school counselors and the effects of non-counseling duties, little attention has been given to rural school counselors who specifically hold formal teaching assignments and how they navigate these dual roles. The purpose of this study was to explore how rural school counselors with other teaching duties overcome challenges and leverage their assets to (1) manage their school counseling programs, (2) impact students, (3) navigate the ambiguity of their job-related situation, and (4) advocate for their professional identities. Guided by role theory, this phenomenological collective case study examined the lived experiences of five rural school counselors in Kansas who also held teaching duties. Semi-structured interviews and cross-case analysis revealed five interconnected themes: availability and time constraints, navigating role conflict, relationships as central to success, rurality and resources, and advocacy and leadership. This study contributes to the literature by identifying strategies participants used to manage dual roles, describing how they leveraged rural assets to address challenges, examining sources of their role ambiguity, and illustrating the flexible and responsive approaches used to advocate for their professional identities. Findings have implications for practicing school counselors, counselor educators, school administrators, policymakers, and related professional organizations, with recommendations related to school counselor preparation, practice, policy, and professional representation.
Keywords: School counseling; Rural education; Dual roles